Establishment and detection of a new S flow model in the pipe of oil–gas lubrication systems - Xiaopeng Xie; Yijun Xiong (AIP Advances)
Due to unique operational characteristics such as intermittent oil supply, trace lubricant supply, and small pipe diameters, oil–air lubrication systems exhibit distinct flow behaviors compared to conventional two-phase flow systems. These specific operational conditions greatly influence the mechanisms underlying flow pattern formation and transition, necessitating targeted research. Under the assumption of constant fluid density within the pipe, this study proposes three flow models—oil film flow, oil droplet flow, and S-shaped flow (S-flow)—with particular emphasis on elucidating the formation mechanism and dynamic characteristics of S-flow. Furthermore, a cost-effective and efficient dual-channel infrared oil-film detection device was developed and used to experimentally validate these proposed flow models and their transitional behaviors. Experimental results confirm that S-flow widely exists under specific operating conditions, highlighting its critical role in ensuring optimal lubrication performance within the pipeline. The outcomes provide a theoretical basis for optimizing lubrication system performance and contribute to a deeper theoretical understanding of multiphase flow behaviors in micro-scale lubrication contexts.